Caregivers’ Attitude towards People with Mental Illness and Perceived Stigma: A Cross-Sectional Study in a Tertiary Hospital in Nepal - Neupane, Dipika; Dhakal, Sarmila; Thapa, Sabita; Bhandari, Parash Mani; Mishra, Shiva Raj (PLOS ONE, 2016)
Background Mental illness is stigmatized in most of the communities and people with such illness are often subjected to defame. Stigma impairs an individual’s and their caregiver’s physical, social and emotional wellbeing, and health-seeking behavior. Sufficient literature on how often the caregivers of people with mental illness from low and middle-income countries are stigmatized and how they perceive people with mental illness is unavailable. In this study, we examined caregivers’ attitude towards people with mental illness and perceived stigma. Methods We conducted face-to-face interviews with 170 caregivers in an outpatient clinic of a hospital in Nepal using a structured questionnaire. We calculated median and inter-quartile range of the attitude and perceived stigma scores. To assess the correlates, Kruskal Wallis H test and Mann Whitney U test were carried out. Results Overall median score for the domains: attitude (score range: 18–90) and perceived stigma (score range: 12–60) were 42 and 28 respectively, inter-quartile range being 8 each. Attitude score differed significantly by the sex of caregiver (p<0.05), educational status of caregiver (p<0.001), sex of patient (p<0.05) and type of mental illness (p<0.05). Perceived stigma score varied significantly by caregiver’s sex (p<0.05), marital status (p<0.001), educational status (p<0.001), occupation (p<0.05), relation with the patient (p<0.005) and use of alternative treatment modalities (p<0.05). Conclusion Sex of participant, educational status, sex of patient and type of mental illness were the correlates of attitude towards mental illness. Similarly, sex of participant, marital status, educational status, occupation, caregiver’s relation with patient and use of alternative treatment modalities were correlates of perceived stigma. Findings of this study suggest that interventions targeting these high-risk populations might be beneficial to help build a positive attitude and overcome the perceived social stigma.